Nanotoxicology and nanoparticle safety in biomedical designs - Ai J (Dove Medical Press, 2011)
Jafar Ai1, Esmaeil Biazar2, Mostafa Jafarpour3, Mohamad Montazeri4, Ali Majdi5, Saba Aminifard5, Mandana Zafari5, Hanie Akbari R6, Hadi Rad Gh71Department of Tissue Engineering, Faculty of Advanced Technologies, Tehran University of Medical Sciences, Tehran; 2Department of Chemistry, Islamic Azad University – Tonekabon Branch, Mazandaran; 3Department of Microbiology, Faculty of Science, Islamic Azad University – Tonekabon Branch, Mazandaran; 4Faculty of Medical Sciences, Babol University of Medical Sciences; 5Young Researchers Club – Islamic Azad University, Tonekabon Branch, Mazandaran; 6Faculty of Medical Sciences, Islamic Azad University – North branch, Tehran; 7Faculty of Medical Sciences, Islamic Azad University – Tonekabon Branch, Mazandaran, IranAbstract: Nanotechnology has wide applications in many fields, especially in the biological sciences and medicine. Nanomaterials are applied as coating materials or in treatment and diagnosis. Nanoparticles such as titania, zirconia, silver, diamonds, iron oxides, carbon nanotubes, and biodegradable polymers have been studied in diagnosis and treatment. Many of these nanoparticles may have toxic effects on cells. Many factors such as size, inherent properties, and surface chemistry may cause nanoparticle toxicity. There are methods for improving the performance and reducing toxicity of nanoparticles in medical design, such as biocompatible coating materials or biodegradable/biocompatible nanoparticles. Most metal oxide nanoparticles show toxic effects, but no toxic effects have been observed with biocompatible coatings. Biodegradable nanoparticles are also used in the efficient design of medical materials, which will be reviewed in this article.Keywords: nanotechnology, nanotoxicology, nanomaterials, nanobiomaterials